In Vitro and In Vivo Effects of Xanthorrhizol on Human Breast Cancer MCF-7 Cells Treated With Tamoxifen - Nattanant Noomhorm; Chun-Ju Chang; Che-Sheng Wen; Jir-You Wang; Jiun-Liang Chen; Ling-Ming Tseng; Wei-Shone Chen; Jen-Hwey Chiu; Yi-Ming Shyr (Elsevier, 2014)
Abstract.: This study investigated the herb-drug interaction of xanthorrhizol and tamoxifen in human breast cancer cells. Using MCF-7 cell line as an in vitro model, the herb-drug interaction between xanthorrhizol and tamoxifen was measured by MTT assay, luciferase reporter assay, and cell cycle analysis. The effects of xanthorrhizol on growth/autophagy related signaling were determined by immunostaining, western blotting, and real time RT-PCR. Additionally, the in vivo effect of xanthorrhizol and tamoxifen on athymic nude mice implanted with MCF-7 cells was evaluated. When MCF-7 cells were co-treated with tamoxifen and xanthorrhizol, there were no significant changes in terms of cell number, luciferase activity, percentage S-phase cells and LC3-II expression. However, using the MCF-7 implanted nude mice model, it was possible to detect significantly increased tumor volumes, a larger tumor size, and increased protein expression of P38 and P27(Kip1) in the xanthorrhizol + tamoxifen group compared to the tamoxifen-alone group. It can be concluded that while there is no significant herb-drug interaction between xanthorrhizol and tamoxifen in vitro, there is such an interaction in tumor-bearing mice, which provides important information that affects breast cancer treatment translational research. Keywords:: breast cancer, tamoxifen, interaction, xanthorrhizol